Disability with dignity : justice, human rights and equal status - Barclay, Linda (Lecturer); Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2019)
Philosophical interest in disability is rapidly expanding. Philosophers are beginning to grasp the complexity of disability as a category, with respect to well-being and as a marker of identity. However, the philosophical literature on justice and human rights has often been limited in scope and somewhat abstract. Not enough sustained attention has been paid to the concrete claims made by people with disabilities, concerning their human rights, their legal entitlements and their access to important goods, services and resources.?This book discusses how effectively philosophical approaches to distributive justice and human rights can support these concrete claims. It argues that these approaches often fail to lend clear support to common disability demands, revealing both the limitations of existing philosophical theories and the inflated nature of some of these demands. Moving beyond entitlements, the author also develops a unique conception of dignity, which she argues illuminates the specific indignities experienced by people with disabilities in the allocation of goods, in the common experience of discrimination and in a wide range of interpersonal interactions.Disability with Dignity offers an accessible and extended philosophical discussion of disability, justice and human rights. It provides a comprehensive assessment of the benefits and pitfalls of theories of human rights and justice for advancing justice for the disabled. It brings the moral importance of dignity to the centre, arguing that justice must be pursued in a way that preserves and promotes the dignity of people with disabilities.
chapter Introduction -- chapter 1 What Is Disability? -- chapter 2 Moving on from Definitional Debates -- chapter 3 A Just Distribution of Resources -- chapter 4 A Just Distribution of Capabilities -- chapter 5 The Distributive Potential of Human Rights -- chapter 6 Capabilities Justice as Human Rights? -- chapter 7 Dignity and the Right to Vote -- chapter 8 Dignity, Day to Day.
Keywords: PHILOSOPHY / Ethics & Moral Philosophy; People with disabilities; Social justice